Mapping the Evolution of Sea Outfall Research: Insights for Marine Environmental Sustainability - Yılmaz, Damla; Yilmaz, Hulya; Erdem, Elif Aybike; Yilmaz, Mustafa Utku; Vaheddoost, Babak; Aras, Egemen (My University, 2025)
Effective management of sea outfall is a critical topic in marine environmental science, sustainability regulations, and adaptation for the road maps. Therefore, the development of sea outfall research is mapped in this study by addressing 248 articles published during 1970 – 2023. A detailed assessment of the field’s evolution is provided through a combination of bibliometric and content analysis. Network analysis techniques, including co-occurrence, co-authorship, citation, and bibliographic coupling, are used to identify dominant research topics, citation patterns, and productive authors and countries. Subsequently, content analysis is applied to investigate the attributes, research methods, and gaps in the existing research. A new and detailed classification of sea outfall research is obtained from the content analysis namely: field studies, laboratory experiments, and data analysis, with consideration to the methodologies applied in the studies (modelling, numerical analysis, experimental techniques, simulation, and field studies). The findings not only highlight the progression of sea outfall research but also offer new perspectives that could inform future research and strategic investments aimed at enhancing marine environmental sustainability and managmenet.
Keywords: VOSviewer; Bibliometric analysis; research policy; sutainability